Citizen Culture, Citizenship and Social Work - Rincón-Salazar, María Teresa (Prospectiva. Revista de Trabajo Social e Intervención Social, 2006)
The article establishes the relationship between the notions of civic culture and citizenship, and it presents hints and relating from one perspective of the Social Work, for think the conception of civic culture starting from the redefinition of elements of a new citizenship.